Promosi Jabatan dan Mutasi : Literatur Review terhadap Kinerja Karyawan - Nadya Nabilla Andansari; Margareta Shintya Devi; Retno Warih Dwi Utami Ningsih; Wiwik Herawati (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
Two critical areas of human resource management that may influence job happiness and performance are mutations and promotions. In the field of human resource management, this research aims to review the literature on the topic of job mutation and promotion. This research systematically reviewed the literature to determine what characteristics affect employee performance and happiness as they pertain to promotions and mutations. Results reveal that placing and promoting mutations may have good or bad impacts depending on how the procedure is executed. Additionally, the research demonstrates that support and mutation are significantly impacted by staff ability, experience, and performance.